Developing a System for Big Data Discovery - Saleh, Sakhr; Eassa, Fathy; Jambi, Kamal (International Journal of Engineering and Technology, 2019)
In this research, we developed a system for collecting metadata of existing Big Data in an enterprise or organization. All collected metadata are stored in metadata storage. The collected Meta Data help in managing the existing Big Data. Also, in this research, we developed a technique for discovering simple knowledge from existing Big Data (Twitter & websites) and extracted the correlation between different Big Data. Since Big Data are distributed across a large number of remote machines, we used a mobile agent technology to build our system for reducing the discovery time. The mobile agent migrate to the remote machine for discovering the required data and in consequence reduce the transportation time.Â